Two dimensional non-destructive testing data maps for reinforced concrete slabs with simulated damage - Harsh Rathod; Rishi Gupta (Data in Brief, 2019)
This research presents the use of a total of five Non-Destructive Testing Techniques (NDTs) and their combination to detect and quantify subsurface simulated defects in Reinforced Concrete slabs. The NDT techniques were applied on a total of nine 1800 mm × 460 mm reinforced concrete slabs with varying thicknesses of 100 mm, 150 mm and 200 mm. Contour data maps from each technique were prepared. This Data article presents the Non-Destructive Testing Techniques’ specifications, experimental set-up and converted 2-Dimensional NDT data maps for reinforced concrete slabs with simulated damage. The experimental research shows that combining multiple techniques together in evaluating the defects give significantly lower error and higher accuracy compared to that from a standalone test. For more details on the accuracy model of the NDTs, refer to the full length article entitled “Sub-surface simulated damage detection using Non-Destructive Testing Techniques in reinforced-concrete slabs” https://doi.org/10.1016/j.conbuildmat.2019.04.223 Rathod et al., 2019. Keywords: Non-destructive testing techniques, Ultrasonic pulse velocity, Infrared thermography, Ground penetrating radar, Half-cell potential, Electrical resistivity, Reinforced concrete structures